Correction of anterior bowing complicating tibial osteofibrous dysplasia in preadolescents by osteotomy and telescopic nailing without lesional resection: a preliminary study of four-case reports - Yanhui Jing; Zhiqiang Zhang; Yueqiang Mo; Dahui Wang; Chunxing Wu; Bo Ning (BMC Musculoskeletal Disorders, 2024)
Abstract Background Osteofibrous dysplasia (OFD) occurs most frequently in the tibia and may result in deformity and pathological fracture. Surgical treatment such as curettage or segment excision has been performed but remains controversial due to high complication rates and surgical burden. This study introduces a new method to manage OFD with anterior bowing of the tibia using minimally invasive tibial osteotomy and telescopic rod (TR) osteosynthesis without extensive lesion resection. Methods A retrospective study of 4 children with OFD and tibia bowing deformity treated with minimally invasive tibial wedge osteotomy and TR fixation between January 2015 and November 2020 was performed. Results including bone healing, complications, function based on MSTS score, and recurrance of deformity were assessed. Results The median follow-up was 29 months. Radiographs showed the median time for union was 3 months. There were no instances of refracture or recurrence of deformity. The mean post-operative MSTS score was significantly higher than preoperative score. Conclusions This method avoids large bone defects and reconstructive procedures. It is an effective and minimally invasive approach for managing anterior bowing deformity secondary to OFD while improving function and quality of life. Level of evidence Level IV; Case Series; Treatment Study.